2006
DOI: 10.1111/j.1472-765x.2006.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profiling andfla-typing of Irish thermophillicCampylobacterspp. of human and poultry origin

Abstract: Aims:  To determine the genetic relationship between a random collection of Irish human and poultry Campylobacter isolates and to determine the frequency of antibiotic resistance. Methods and Results:  Sixty‐six Campylobacter isolates (34 human and 32 poultry) were typed by restriction fragment length polymorphism of flagellin‐A (flaA) PCR products (flaA‐RFLP) and by sequencing of the short variable region of flaA (flaA‐SVR). FlaA‐RFLP identified 58 distinct profiles, while flaA‐SVR identified 28 different all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
6
16
2
Order By: Relevance
“…This result agrees with the previous studies which suggested that none of C. jejuni isolates from humans and companion animals was resistant [16,28]. However, other studies reported 3-6.8% of erythromycin resistance in C. jejuni isolated from humans [7,18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result agrees with the previous studies which suggested that none of C. jejuni isolates from humans and companion animals was resistant [16,28]. However, other studies reported 3-6.8% of erythromycin resistance in C. jejuni isolated from humans [7,18].…”
Section: Discussionsupporting
confidence: 81%
“…can be recognized as a major public health concern [7,23]. In this study, the prevalence of antimicrobial resistance in Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…tested by participating laboratories worldwide during 2005 to 2006, 26.5% were resistant to ampicillin. Corcoran et al (4) reported that ampicillin resistance was prevalent (48.5%) among Irish isolates of Campylobacter spp. and that the incidence of antimicrobial resistance in poultry isolates was higher than in those from humans.…”
mentioning
confidence: 99%
“…are considered as one of the major causative agents of acute gastro-enteritis in both humans and animals (Al-Mahmeed et al 2006;Allos 2001;Corcoran et al 2006;Feodoroff et al 2009). The clinical manifestations of the enteritis caused by Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%